1989
DOI: 10.7164/antibiotics.42.1562
|View full text |Cite
|
Sign up to set email alerts
|

Altemicidin, a new acaricidal and antitumor substance. II. Structure determination.

Abstract: The structure of altemicidin, a new acaricidal and antitumor agent, was determined to be (l^,25,3a^,7a5)-4-carbamoyl-2-hydroxy-6-methyl-l-(sulfamoylacetamido)-2,3,3a,6,7,7a-hexahydro-6-azaindene-l-carboxylic acid by a combination of spectroscopic and X-ray crystallographic analysis of its derivatives.Altemicidin is a monoterpene alkaloid.Altemicidin, isolated from a culture broth of an actinomycete strain identified as Streptomyces sioyaensis SA-1758, is a new compound having the acaricidal and antitumor activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
2

Year Published

1992
1992
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 9 publications
0
29
0
2
Order By: Relevance
“…Addition of an isoleucyl fragment to altemicidin increases its molecular weight to 489, the observed molecular weight of (1) and further addition of a /3-methyrphenylalanyl fragment increases the molecular weight to 650, that determined for (2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Addition of an isoleucyl fragment to altemicidin increases its molecular weight to 489, the observed molecular weight of (1) and further addition of a /3-methyrphenylalanyl fragment increases the molecular weight to 650, that determined for (2).…”
Section: Resultsmentioning
confidence: 99%
“…The structure determination studies of these compounds are reported in this paper. The structures of (1), (2) and (3) as well as the structures of (4) and (5), two triacetylated analogues of (2), are shown in Fig. 1.…”
Section: -Methylpentanoyl)aminosulphonyl]mentioning
confidence: 99%
See 1 more Smart Citation
“…Streptomyces sioyaensis SA-1758 was isolated from sea mud collected at Gamo, Miyagi Prefecture, Japan. The strain SA-1758 produced a monoterpene-alkaloid, altemicidin (Takahashi et al 1989a). The compound strongly inhibited the growth of L1210 and carcinoma IMC cell lines with IC50 values of 0.84 and 0.82 μg/mL, respectively (Takahashi et al 1989b).…”
Section: Isoprenoidsmentioning
confidence: 99%
“…Altemicidin (Figure 11) with a monoterpene-alkaloid skeleton is produced by S. sioyaensis SA-1758 isolated from sea mud collected at Gamo, Miyagi Prefecture, Japan [135]. This compound was found to inhibit the growth of murine lymphoid leukemia L1210 and carcinoma IMC cell lines with IC 50 values of 0.84 and 0.82 μg/mL, respectively, although it showed high acute toxicity in mice [136].…”
Section: Isoprenoidsmentioning
confidence: 99%